Thyroglossal duct carcinoma - Abdullah, Kahairi; Raja Lope Ahmad, Raja Ahmad Al'konee; Leman, Wan Ishlah; H, Hasmah (Singapore Medical Association, 2009)
We report a 56-year-old Malay woman with a tumour that involved the skin and caused hyoid bone erosion. There was no clinical or radiological evidence of regional lymph node involvement. A modified radical neck dissection with preservation of the accessory nerve and internal jugular vein was performed, followed by an "extended" Sistrunk operation. The surgical defect was reconstructed with a pectoralis major myocutaneous flap. Our literature review showed that this is the first reported thyroglossal duct carcinoma which involved the skin and required a pedicle flap reconstruction.